2018
DOI: 10.1149/2.1301814jes
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Gamma Irradiation on a Fatty Acid Self-Assembling Coating of Copper

Abstract: Self-assembled molecules (SAMs) form layers on copper that have an advantage compared to traditional corrosion inhibitors because of the significant decrease of chemical application. The protective properties of such films can be improved by different procedures of application of the SAM layer. In this work, a SAM layer of elaidic acid, a monounsaturated long-chain fatty acid with trans geometrical configuration, was applied on copper surface. Gamma irradiation was used to improve the protective properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[ 17 ] It has been shown that in the presence of oxygen, even low doses of radiation up to 10 kGy enhance the protective properties of SAMs by increasing the adsorption of FA molecules on the surface. [ 6 ] A similar observation was made for SAMs of amphiphilic undecenylphosphonic acid molecules on carbon steel, [ 18 ] but the authors incorrectly inferred crosslinking of the film. In fact, crosslinking was not possible because irradiation was done in the presence of oxygen, which is known to induce cleavage reactions under the conditions studied.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…[ 17 ] It has been shown that in the presence of oxygen, even low doses of radiation up to 10 kGy enhance the protective properties of SAMs by increasing the adsorption of FA molecules on the surface. [ 6 ] A similar observation was made for SAMs of amphiphilic undecenylphosphonic acid molecules on carbon steel, [ 18 ] but the authors incorrectly inferred crosslinking of the film. In fact, crosslinking was not possible because irradiation was done in the presence of oxygen, which is known to induce cleavage reactions under the conditions studied.…”
Section: Introductionmentioning
confidence: 65%
“…EA was applied on the copper surface according to the procedures proposed earlier. [5,6] As carboxylic acids are known to preferentially bind on metallic oxides, thermal oxidation of copper's surface is an important step prior to EA application. It has also been shown previously that heating of the fatty acid solution has a positive effect on the layer stability, as well as drying at higher temperatures after SAM application.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special atmospheric conditions (e.g., ozone) can destroy the thiol SAM nanolayers, when the thiolat head group is transformed to sulfonate. Other researcher explained that the ozonolysis can occur under the influence of UV light at wavelength of 185 nm and 254 nm [ 57 , 58 , 59 ].…”
Section: Self-assembled Nanolayersmentioning
confidence: 99%